CIRCUITOS MOTRICES PARA EL MEJORAMIENTO DE LA CONDICIÓN FÍSICA DE LOS ESTUDIANTES DE SEGUNDO AÑO DE EGB DE LA UNIDAD EDUCATIVA “PEDRO LEOPOLDO BALLADARES” DEL CANTÓN URDANETA - VERGARA GRANADOS JOSEPH GUILLERMO (2024)
The objective of this work was to analyze the contribution of motor circuits to the improvement of the physical condition of second-year EGB students at the “Pedro Leopoldo Balladares” Educational Unit in the Urdaneta canton. At the “Pedro Leopoldo Balladares” Educational Unit in the Urdaneta canton, a worrying deficiency has been observed in the physical condition of second-year students of Basic General Education (EGB) who present low levels of resistance, muscular strength, flexibility and motor coordination, which not only affects the physical well-being of students, but also has negative repercussions on their ability to actively participate in school activities. A non-experimental methodology of a mixed nature was used with a descriptive type of research in which techniques such as observation and interview were used, which had as instruments the observation sheet and the questionnaire. The results of the research demonstrate that it is feasible to implement motor circuits so that second-year students can improve considerably. In conclusion, the assessment of the students' physical condition revealed that there are difficulties in maintaining intensity during the performance of motor circuits, participating in activities, endurance, catching and completing cone circuits with changes, which derives from a lack of regular physical activity. Therefore, it is proposed to regularly apply motor circuits to strengthen the students' physical condition